2017
DOI: 10.1002/slct.201702090
|View full text |Cite
|
Sign up to set email alerts
|

Peroxydisulfate as an Oxidant in the Site‐Selective Functionalization of sp3 C–H Bonds

Abstract: The development of methodology for the site-selective functionalization of sp 3 C-H bonds has irrevocably altered the state of organic synthesis. These methods often rely on the use of strong oxidants in conjunction with transition-metal catalysis. Peroxydisulfate (S 2 O 8 2-) salts are some of the strongest inorganic oxidants known. They are low-cost crystalline solids that are stable at room temperature. Harmless sulfate salts are produced as a byproduct of their reactions, allowing S 2 O 8 2to serve as a 'g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 90 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…On the basis of the above results and related literature, ,, a possible mechanism for the palladium-catalyzed C–H oxidative fluoroalkoxylation of benzaldehydes was proposed (Figure ). First, benzaldehyde and amino acid A6 reversibly form imine intermediate A . Meanwhile, the active Pd­(II) species is generated in situ from Pd­(OAc) 2 with TFA .…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…On the basis of the above results and related literature, ,, a possible mechanism for the palladium-catalyzed C–H oxidative fluoroalkoxylation of benzaldehydes was proposed (Figure ). First, benzaldehyde and amino acid A6 reversibly form imine intermediate A . Meanwhile, the active Pd­(II) species is generated in situ from Pd­(OAc) 2 with TFA .…”
mentioning
confidence: 61%
“…To gain insight into the reaction mechanism, we independently synthesized the putative palladacycle intermediate (eq ). Pleasingly, the cyclopalladium intermediate 6 was isolated from the reaction system of benzaldehyde with stoichiometric Pd­(OAc) 2 , pyridine, and A6 . , Then, the cyclopalladium intermediate 6 was treated with TFE, K 2 S 2 O 8 , and TFA to give 3a in 55% yield (eq ). Subsequently, kinetic isotope effect (KIE) experiments were performed (eqs and ).…”
mentioning
confidence: 99%
“…The economical and safe persulfate salts (PSs) have also been extensively used for hydroxylation, fluorination, cyclization, and coupling reactions. In general, SO 4 •– produced during PS activation is an important oxidizing species in the oxidation of various substrates. , For instance, SO 4 •– not only hydroxylates fluorobenzene and toluene to the corresponding p -fluorophenol and cresol but also decarboxylates 2-biphenyl acetic acid to the benzyl radical, which then undergoes intramolecular cyclization to yield fluorene . Ma et al also suggested that SO 4 •– activated the benzylic C–H and facilitated its further fluorination to benzylic C–F by Selectfluor.…”
Section: Introductionmentioning
confidence: 99%
“…Persulfate salts are inexpensive, widely available crystalline solids that are very soluble in water and reasonably soluble in aqueous acetonitrile, small chain alcohols, and acetone and are beginning to attract interest in organic synthesis [34–38] . The peroxydisulfate ion (S 2 O 8 2− ) is a strong oxidant with an estimated standard redox potential of 2.01 V, this being higher than that of other peroxygen‐containing compounds such as hydrogen peroxide or sodium bisulfite.…”
Section: Introductionmentioning
confidence: 99%